The Effect of Pollution Source Distance, Construction, and Behavior of Dug Well Users on Total Coliform Content - Kirana Nurul Arifiani; Sunarto Sunarto; Siti Rachmawati (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Dug well is a water source that is located relatively close to the ground surface so it is prone to pollution. This research aims to analyze the effect pollution source distance, construction and behavior of dug well users on total coliform content in Karangturi Village. Data collection was carried out by examining samples of dug well water in the laboratory, observing and measuring well construction, and using questionnaires to measure the behavior of well users. The research results show that 23 (95.8%) wells have a total coliform >0 MPN/100ml and 1 (4.2%) well have a total coliform content of 0 MPN/100ml. Simultaneously (p value=0.106) the variable distance to the pollutant source and partially (p value= 0.998) each livestock pen and septic tank variable do not have a significant influence on the total coliform content. Simultaneous well construction (p value= 0.489) and partially (p value= 0.999) of each well construction variable did not have a significant effect on the total coliform content. The behavioral variable simultaneously (p value= 0.346) and partially the knowledge variable (p value= 1.000), the attitude variable (p value= 0.999), and the attitude variable (p value= 0.999) did not have a significant effect on the total coliform content.